Management protocols of the hot tooth-A KAP survey among general dentists and endodontists - Anupama Ramachandran; Sulthan I R Khan; Salman Siddeeqh; Pillai A Gopinathan; Laliytha K Bijai; Kiran Iyer (Wolters Kluwer Medknow Publications, 2023)
Aim: Pain management is a cornerstone in the practice of endodontics. However, optimum pain control has been a challenge in cases of symptomatic irreversible pulpitis resulting in a "hot tooth." Thus, the objective of the study is to assess the knowledge and attitude and to determine the clinical protocols of "hot tooth" management followed among general practitioners and specialists. Materials and Methods: The KAP questionnaire contained 05 knowledge, 04 attitudes, and 06 practice-related items. The questionnaire was pretested among 10 randomly selected general dentists and endodontists. Testing-retesting was also performed. The questionnaire was self-administered and the acceptance to answer the questionnaire was considered consent to participate in the study. The sample size was calculated to be 200 with a 95% level of confidence. Descriptive statistics were used. For significance level, P < 0.05 was considered statistically significant. The Chi-square test was used for comparison between the endodontists and the general dentists. Results: The anesthetic techniques that clinicians are most skilled in are infiltration and inferior alveolar nerve block (IANB) - 96.6% and 98.5% respectively. The intraosseous technique (IO) was the least preferred technique (6.8%). The most common supplementary injection used among both the BDS and MDS graduates was intrapulpal anesthesia. In cases of acute pulpitis, 54% of the respondents prescribed NSAIDs as a pre-anesthetic medication. Conclusion: The current study shows that supplemental injections like intraosseous and intraligamental techniques are underutilized. Also, the benefits of preanesthetic medication for hot tooth management are not harnessed among clinicians despite the sufficient body of evidence.